High detection rates of pancreatic cancer across stages by plasma assay of novel methylated DNA markers and CA 19-9 - Majumder, Shounak (Clin Cancer Res, 2021)
BACKGROUND & AIMS: We have previously identified tissue methylated DNA markers (MDMs) associated with pancreatic ductal adenocarcinoma (PDAC). In this case-control study, we aimed to assess the diagnostic performance of plasma MDMs for PDAC. METHODS: Thirteen MDMs (GRIN2D, CD1D, ZNF781, FER1L4, RYR2, CLEC11A, AK055957, LRRC4, GH05J042948, HOXA1, PRKCB, SHISA9, and NTRK3) were identified based on selection criteria applied to results of prior tissue experiments and assays were optimized in plasma. Next, 340 plasma samples (170 PDAC cases, 170 controls) were assayed using target enrichment long-probe quantitative amplified signal method. Initially, 120 advanced stage PDAC cases and 120 healthy controls were used to train a prediction algorithm at 97.5% specificity using random forest (rForest) modeling. Subsequently, the locked algorithm derived from the training set was applied to an independent blinded test set of 50 early stage PDAC cases and 50 controls. Finally, data from all 340 patients were combined, and cross-validated. RESULTS: The cross-validated AUC for the training set was 0.93 (0.89−0.96) for the MDM panel alone, 0.91 (95% CI: 0.87–0.96) for CA 19–9 alone, and 0.99 (0.98−1) for the combined MDM-CA 19–9 panel. In the test set of early stage PDAC, the AUC for MDMs alone was 0.84 (0.76–0.92), CA19–9 alone was 0.87 (0.79–0.94), and combined MDM-CA 19–9 panel was 0.90 (0.84–0.97) significantly better compared to either MDMs alone or CA19–9 alone (p=0.0382 and 0.0490, respectively). At a pre-set specificity of 97.5%, the sensitivity for the combined panel in the test set was 80% (28–99%) for stage 1 disease and 82% (68–92%) for stage 2 disease. Using the combined data sets, the cross-validated AUC was 0.9 (0.86−0.94) for the MDM panel alone and 0.89 for CA 19–9 alone (0.84–0.93) vs 0.97 (0.94−0.99) for the combined MDM-CA 19–9 panel, p≤0.0001 Overall, cross-validated sensitivity of MDM-CA 19–9 panel was 92% (83–98%) with an observed specificity of 92% at the preset specificity of 97.5%. CONCLUSIONS: Plasma MDMs in combination with CA 19–9 detect PDAC with significantly higher accuracy compared to either biomarker individually.